The needs based evaluation of ESP material English course for nursing students for second year students at Thanh Hoa Medical College = Đánh giá dựa theo nhu cầu tài liệu tiếng Anh chuyên ngành “english course for nursing students” dành cho sinh viên năm t - Nguyễn, Thị Vân (University of Languages and International Studies, 2017)
36 p. + CD-ROM